Posted by **Sejul** on Saturday, November 12, 2011 at 9:03pm.

solve 3^(2x+1) = 9^(2x-1)

using base 3 logs

## Answer this Question

## Related Questions

- Math - Logs are stacked up in apile as shown in the figure. The top row has 15 ...
- math - natural logs - Find the EXACT solution to e^(1-x) = 4^x You must use logs...
- Precalculus - .5=e^(-20t) I am assuming this involves logs but we did't really ...
- math - how do you solve for x using logs: [(a + b)^x]/b^x I am not sure of the ...
- math-logs - 1. logaB = 2 and logbC = 4, evaluate logcA *the lowercase letters ...
- LOGARITHMS - HI THE QUESTION STATES THAT ONE SHOULD CALCULATE THE LOGS WITHOUT ...
- Exponents and Logs (Math) - Solve for x: 2^(-x+1) = 4(8^x) I try isolating the 4...
- Maths (Logs) - 1.Write the following equation without logs log y = mx+ c This ...
- algebra - solve e^x / 3 = 5^x using logs.
- maths - solve for x 8=6^x using logs